Evaluating surface water–groundwater interactions in floodplains using SWAT+ and gwflow - Schulz, Evan, author; Morrison, Ryan R., advisor; Bailey, Ryan T., advisor; Wohl, Ellen, committee member (Colorado State University. Libraries, 2023)
Floodplains are essential ecosystems that provide a variety of economic, hydrologic, and ecologic services. Within floodplains, surface water-groundwater exchange plays an important role in facilitating biogeochemical processing and can have a strong influence on hydrology through infiltration or discharge of water. These functions can be difficult to assess due to the heterogeneity of floodplains and monitoring constraints, so numerical models are useful tools to estimate fluxes, especially at a large scale. In this study, the gwflow module of the SWAT+ (Soil and Water Assessment Tool) ecohydrological model quantified magnitudes and spatiotemporal patterns of floodplain surface water-groundwater exchange in a mountainous watershed using an updated version of the module that directly calculated floodplain-aquifer interactions during periods of floodplain inundation. The gwflow module is a spatially distributed groundwater modeling subroutine within the SWAT+ code that uses a gridded network and physically based equations to calculate groundwater storage, groundwater head, and groundwater fluxes. I used SWAT+ to model an area of 7,516 km2 in the Colorado Headwaters HUC8 watershed (14010001) and used streamflow data from USGS gages in the watershed for calibration and testing. I evaluated model performance for scenarios with and without simulated floodplain-groundwater exchange and for three gwflow grid cell sizes. Models that included floodplain-groundwater interactions outperformed those without such interactions and provided valuable information about floodplain inundation and exchange rates. Furthermore, I found that smaller gwflow cell sizes showed similar or better performance than larger cell sizes and simulated additional information about local variations in groundwater fluxes, especially within floodplains. Finally, my analyses on the location of floodplain fluxes in the watershed showed that wider areas of floodplains, "beads," exchanged a higher net and per area volume of water, as well as higher rates of exchange, than narrower areas, "strings." These outputs remained consistent across all studied cell sizes, with smaller cells simulating greater differences between bead and string floodplain regions. Study results show that floodplain surface water-groundwater exchange is a valuable process to include in hydrologic models, and model outputs could inform land conservation practices by indicating priority locations where substantial hydrologic exchange occurs.
Keywords: floodplain; gwflow; Colorado; SWAT; groundwater